The methylisothiazolinone epidemic goes along with changing patients' characteristics – After cosmetics, industrial applications are the focus. (17th November 2019) - Schnuch, Axel; Schubert, Steffen; Lessmann, Holger; Geier, Johannes
Abstract: Background: Sensitization to methylisothiazolinone (MI) has seen an exceptional epidemic, mainly attributed to its use in cosmetics. Objectives: To trace the epidemic of MI allergy (2009–2018), and to analyze a possible change of patients' characteristics. Methods: Informationsverbund Dermatologischer Kliniken‐data of patients patch tested between 2009 and 2018 with MI (0.05% aq.) were analyzed concerning anamnestic items and sensitization frequencies. Results: Overall, 4.9% reacted positive to MI. Comparing sensitization to MI in three periods (2009, 2013/14, and 2017/18), there was an increase to 7% in 2013 and a decrease to 3.4% in 2018. The MOAHLFA Index (M=Men, O=Occupational Dermatitis, A=Atopic Dermatitis, L=Leg Dermatitis, F=Face Dermatitis, A= Age > 40) for the period 2013/14 is characterized by a lower proportion of occupational dermatitis and a higher proportion of face dermatitis. The period 2017/18 is characterized by increases of occupational dermatitis and hand dermatitis, and a decrease of face dermatitis. Painters, personal care workers, and hairdressers were particularly affected. Sensitization in hairdressers and personal care workers (mostly cosmeticians) decreased after the peak in 2013/14, whereas sensitization to MI in painters continued to increase. Conclusions: After an unprecedented epidemic of MI allergy, mainly caused by its use in cosmetics, the continuous use of MI in industrial applications, for example, paints, and subsequent sensitization remain a matter of concern. Highlights: After an epidemic of MI allergy mainly caused by its use in cosmetics, the continuous use of MI in industrial applications, for example, paints, and subsequent sensitization remain a matter of concern.